Then prove that a = t - q upon r - p
Attachments:
![](https://hi-static.z-dn.net/files/d63/07a6e03dc6b2732696d15b4ba6c25792.jpg)
Answers
Answered by
1
hey check this out the answer
Attachments:
![](https://hi-static.z-dn.net/files/d9a/3469553faebd9a13b26603932384bb25.jpg)
khushi536:
Ty so much
Answered by
1
since x-a is common factor to both polynomials hence on putting x=a ...both polynomials will give same output...
therefore.. put x=a
![{a}^{2} + pa - q = {a}^{2} + ar - t \\ pa - q = ar - t \\ a(p - r) = q - t \\ a = (q - t) \div (p - r) \\ a = (t - q) \div (r - p) {a}^{2} + pa - q = {a}^{2} + ar - t \\ pa - q = ar - t \\ a(p - r) = q - t \\ a = (q - t) \div (p - r) \\ a = (t - q) \div (r - p)](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B2%7D++%2B+pa+-+q+%3D++%7Ba%7D%5E%7B2%7D++%2B+ar+-+t+%5C%5C+pa+-+q+%3D+ar+-+t+%5C%5C+a%28p+-+r%29+%3D+q+-+t+%5C%5C+a+%3D++%28q+-+t%29++%5Cdiv+%28p+-+r%29+%5C%5C+a+%3D+%28t+-+q%29+%5Cdiv+%28r+-+p%29)
here is ur answer.... mark as brainliest if helped
therefore.. put x=a
here is ur answer.... mark as brainliest if helped
Similar questions